Posmodernisme dalam Cerpen âDi Tempatmu Berbaring Sekarangâ Karya Aan Mansyur - Cantini, Cucum (JURNAL PESONA, 2017)
AbstractThis study is an analysis of short story written by Aan Manshur entitled "Di Tempatmu Berbaring Sekarang" which is identical to postmodernist fiction. The analysis leads to identification that paving the way for repertoires on a strategy of ontological emphasis marking the starting point of postmodern fiction. Referring to the beginning of postmodernism, there are criteria of postmodern fiction, in form of words category, construction, words, and foundations. The literary text can be fully understood only through the application of a three-dimensional model: (1) the dimension of speech and position, (2) the dimension of meaning and reference, and, (3) the dimension of the organized text. In this case, the three sequences are reversed, the world categories inferred from an organized dimension of text; the categories of words inferred from dimensions of meaning and reference, and the construction categories inferred from a dimension of speech and position.Keywords: postmodernism, ontological, epistemological, Brian McHale.